KESESUAIAN POLA CELANA SISTEM CHARMANT PADA WANITA DEWASA DENGAN BENTUK PANGGUL â€œSâ€ - DAHLIA, DAHLIA; Zahri, Wildati; Yasnidawati, Yasnidawati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
Problems on the pattern Charmant system tailored pants in adult womenwith pelvic shape S contained in 1) Waist circumference, 2) front waist line, 3)rear waist line, 4) Ring sit, 5) Line sides of the pelvis, and 6) High pesak . Thepurpose of this study is to look at 1) Lack / weakness in pants pattern Charmantsystem in adult women Indonesia with pelvic shape S; 2) How to correctdeficiencies pants pattern Charmant system in Indonesian adult women withpelvic shape S; 3) Suitability of the pattern pants Charmant system in Indonesianadult women with pelvic shape S. This research is applied research. The methodused in this research is descriptive method. The object of research is the patternpants Charmant system that is in fitting 3 times in adult women with pelvic Sshape 22-year-old, with panelists 5 lecturers who are experts in pattern making.The research data collection techniques obtained by spreading the researchinstrument which is based on such assessment formatting Gutman scale, whiledata analysis technique used is descriptive analysis of percentages, this method isused to determine the highest percentage in the conformity assessment systemspants patterns in adult women Charmant Indonesia with form pelvic S. resultsstated there are flaws in the system pants pattern Charmant on loose waistcircumference of 1.5 cm, the front waist line rose 1.5 out of bounds down themiddle, rear waist line up 1 cm from the middle of the rear boundary, crampedseating ring 1, 5 cm, the line side of the pelvis forward 1.5 cm, and a length of 1cm high pesak. Deficiencies remedied by fitting techniques so that the patternpants Charmant system are included conformity with adult women with pelvicshape S.Kata kunci: Kesesuaian Pola Celana Sistem Charmant Pada Wanita DewasaDengan Bentuk Panggul S.